Atherosclerosis Induced by Chlamydophila pneumoniae: A Controversial Theory - Hamidreza Honarmand (Interdisciplinary Perspectives on Infectious Diseases)
More than a century ago, inflammation and infection were considered to have atherogenic effects. The old idea that coronary heart disease (CHD) possibly has an infectious etiology has only reemerged in recent years. Atherosclerosis is the main pathological process involved in CHD and is, logically, the first place to look for infectious etiology. The process of atherosclerosis itself provides the first hints of potential infectious cause. Smooth muscle proliferation, with subsequent intimal thickening, luminal narrowing, and endothelial degeneration, constitutes the natural history of atherosclerosis, being with the severity and speed of these changes. Both viral and bacterial pathogens have been proposed to be associated with the inflammatory changes found in atherosclerosis. Recently, Chlamydophila pneumoniae (C. pneumoniae) has been implicated as a possible etiologic agent of coronary artery disease and atherosclerosis. New evidence which supports a role for C. pneumoniae in the pathogenesis of atherosclerosis has emerged. C. pneumoniae has been detected in atherosclerotic arteries by several techniques, and the organism has been isolated from both coronary and carotid atheromas. Recent animal models have suggested that C. pneumoniae is capable of inducing atherosclerosis in both rabbit and mouse models of atherosclerosis. Furthermore, human clinical treatment studies which examined the use of antichlamydial macrolide antibiotics in patients with coronary atherosclerosis have been carried out. The causal relationship has not yet been proven, but ongoing large intervention trials and research on pathogenetic mechanisms may lead to the use of antimicrobial agents in the treatment of CHD in the future.